Ethnozoology in Traditional Marriage Ceremony of Mandailing Tribe in North Sumatra - Jamilah Nasution (Journal of Tropical Ethnobiology, 2022)
Ethnozoological studies can make an important contribution in the introduction of animal natural resources, especially the use of animals based on local wisdom in the traditional marriage ceremony of the Mandailing tribe in North Sumatra. The Mandailing tribe is one of the tribes that has a uniqueness in traditional marriage ceremonies. Mandailing customs, both in everyday life and in certain traditional ceremonies, are still used by the Mandailing people based on dalihan na tolu. The traditional Mandailing wedding procession begins with a markobar event, an event to bring the bride and groom to the building's highway, awarding titles, and upa-upa. In the ceremony, there are five types of animals used, namely (Bubalus bubalis), Goat (Capra aegagrus hircus), Chicken (Gallus gallus domesticus), Goldfish (Cyprinus carpio), and Shrimp (Caridea). The five types of animals have their own meaning.